2023
DOI: 10.3390/ijms24044127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 16S rRNA Gene Sequence of Nasopharyngeal Exudate Reveals Changes in Key Microbial Communities Associated with Aging

Abstract: Functional or compositional perturbations of the microbiome can occur at different sites, of the body and this dysbiosis has been linked to various diseases. Changes in the nasopharyngeal microbiome are associated to patient’s susceptibility to multiple viral infections, supporting the idea that the nasopharynx may be playing an important role in health and disease. Most studies on the nasopharyngeal microbiome have focused on a specific period in the lifespan, such as infancy or the old age, or have other lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…was not significantly different in any case when comparing between age groups in the uninfected cohort used as a control in this study (18). Similarly, analysing bacterial species richness in the nasopharynx of subjects of the different age and COVID-19 disease severity groups established for this study, revealed no age-or severity-associated relevant differences in alpha diversity, with the only striking exception of COVID-19 patients with severe symptoms, whose alpha diversity decreased progressively as their age increased.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…was not significantly different in any case when comparing between age groups in the uninfected cohort used as a control in this study (18). Similarly, analysing bacterial species richness in the nasopharynx of subjects of the different age and COVID-19 disease severity groups established for this study, revealed no age-or severity-associated relevant differences in alpha diversity, with the only striking exception of COVID-19 patients with severe symptoms, whose alpha diversity decreased progressively as their age increased.…”
Section: Discussionmentioning
confidence: 62%
“…3c). In addition, we have previously demonstrated the absence of any significant changes in alpha diversity in the uninfected control cohort (18).…”
Section: Covid-19 Patientsmentioning
confidence: 80%
See 3 more Smart Citations